Aging power delivery infrastructures - Willis, H. Lee, 1949-, author; Schrieber, Randall R., author (Boca Raton : CRC Press/Taylor & Francis)
"This book looks at the basics of equipment aging and its system and business impacts on utilities. It covers various maintenance, service and retrofit methods available to mitigate age-related deterioration of equipment. It presents numerous configuration and automation upgrades at the system level that can deal with higher portions of aging equipment in the system and still provide good service at a reasonable cost"--